Total Flavonoids of Rhizoma Drynariae Promotes Differentiation of Osteoblasts and Growth of Bone Graft in Induced Membrane Partly by Activating Wnt/β-Catenin Signaling Pathway - Li, Shuyuan; Zhou, Hongliang; Hu, Cheng; Yang, Jiabao; Ye, Jinfei; Zhou, Yuexi; Li, Zige; Chen, Leilei; Zhou, Qishi (Frontiers in Pharmacology, 2021)
Total flavonoids of Rhizoma drynariae (TFRD), a Chinese medicine, is widely used in the treatment of fracture, bone defect, osteoporosis and other orthopedic diseases, and has achieved good results. Purpose of this trial was to explore effects of TFRD on bone graft mineralization and osteoblasts’ differentiation in Masquelet induced membrane technique in rats. Forty male Sprague-Dawley rats were randomly divided into high dose group (H-TFRD), middle dose group (M-TFRD), low dose group (L-TFRD) and control group (control). The critical size bone defect model of rats was established with 10 rats in each group. Polymethyl methacrylate (PMMA) spacer was implanted into the defect of right femur in rats. After the formation of the induced membrane, autogenous bone was implanted into the induced membrane. After 12 weeks of bone graft, bone tissues in the bone graft area were examined by X-ray, Micro-CT and hematoxylin-eosin (HE) and Masson trichrome staining to evaluate the growth of the bone graft. The β-catenin, c-myc, COL1A1, BMP-2 and OPN in bone graft were quantitatively analyzed by Western Blot and Immunohistostaining. Osteoblasts were cultured in the culture medium containing TFRD. Cell Counting Kit-8 (CCK-8) method, Alkaline phosphatase (ALP) and Alizarin Red S (ARS) staining, Western blot, RT-PCR and other methods were used to evaluate the effects of TFRD on the proliferation of osteoblasts and the regulation of Wnt/β-catenin signaling pathway. In vivo experiments showed that the growth and mineralization of bone graft in TFRD group was better. Moreover, the expression of Wnt/β-catenin and osteogenesis-related proteins in bone tissue of TFRD group was more than that in other groups. In vitro experiments indicated that osteoblasts proliferated faster, activity of ALP was higher, number of mineralized nodules and proteins related to osteogenesis were more in TFRD group. But blocking Wnt/β-catenin signaling pathway could limit these effects. Therefore, TFRD could promotes mineralization of bone graft and differentiation of osteoblasts in a dose-dependent manner during growing period of the bone graft of induced membrane technique, which is partly related to the activation of Wnt/ β-catenin signaling pathway.